Theoretical analysis of dynamic pressure propagation in the pore fluids of soils - Fead, J. W., author; U.S. Naval Civil Engineering Laboratory, publisher (Colorado State University. Libraries, 1965)
A study has been made of the propagation of pressure waves through the pore fluid of a soil. Dry, saturated, and partially saturated cases are considered for chesive and cohesionless soils. Tentative recommendations are made concerning assumptions to be made and methods to be used in predicting the pore pressures resulting from impulsive loadings.
CER65JWF43.
October 1965.
Technical Note N-776.
Project No. Y-F008-08-03-402.
Keywords: Soil mechanics; Pressure